Estimate of choline nutritional requirements for chicks from 1 to 21 days of age - de Lima, M. B.; da Silva, E. P.; Pereira, R.; Romano, G. G.; de Freitas, L. W.; Dias, C. T.S. [UNESP]; Menten, J. F.M. (My University, 2018)
Choline is an essential nutrient in poultry diets because it performs various important metabolic functions. The objective of this study was to re-evaluate the choline requirements of male broiler chickens from 1 to 21 days of age at two levels of methionine. Two assays using 2,160 Cobb® chickens (1,080 in each assay) were conducted. The study design was completely randomized and consisted of six treatments and six replicates, with 30 animals per experimental unit. The semipurified basal diet was formulated with corn, soya bean meal, soya protein concentrate, starch and sugar, providing 390 mg/kg choline and 0.593% digestible methionine (requirement level) in Assay 1 and a reduction of about one-quarter in the requirement level of digestible methionine (0.440%) in Assay 2. Choline chloride (62.5%) was added by a supplementation technique to both basal diets to compose crescent levels of choline supplementation (715, 1,040, 1,365, 1,690 and 2,015 mg/kg). The weight gain responses were fitted using quadratic polynomial (QP) and broken-line (BL) models. The ideal intake of choline (mg/bird.day) was estimated from the first intercept of the QP with the BL plateau (BL + QP). The results showed that the diet with the 25% reduction in digestible methionine limited the maximum weight gain by approximately 10%. The choline requirements of broilers from 1 to 7, 1 to 14 and 1 to 21 days of age were 27,013, 44,458 and 62,535 mg/bird.day, respectively, for the requirement level of digestible methionine and 26,796, 41,820 and 56,578 mg/bird.day for the broilers receiving the diet with the 25% reduction in digestible methionine.
Keywords: broiler; dose–response; methyl group donors; nutritional requirements; weight gain